2018
DOI: 10.1002/ca.23293
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the seminal vesicle system for transurethral seminal vesiculoscopy

Abstract: Because of a general lack of knowledge regarding the precise anatomy of the seminal vesicle system, efforts to use transurethral seminal vesiculoscopy (TSV) are currently constrained. We investigated 26 normal adult male specimens. Contrast medium was injected into the seminal vesicle system in 18 specimens and the openings of the ejaculatory ducts were examined with an operating microscope. India ink was injected into the urethra in four specimens to investigate the function of the ejaculatory duct valve. Ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Currently, identifying the location of the ejaculatory duct opening and making an approach for TSV is controversial. Some scholars assert that the ejaculatory duct openings are located at the 5 o'clock and 7 o'clock positions of the seminal colliculus cavity (prostatic utricle) [8,17,18]. Wang et al [19] performed transurethral procedures for 86 patients with benign prostatic hyperplasia or urethral stricture and simultaneously performed transrectal seminal vesicle massage and observed the ejaculatory There were no significant differences in the complications between the two groups (all p > 0.05), but the differences in surgical validity rates between the two groups were statistically significant (*p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, identifying the location of the ejaculatory duct opening and making an approach for TSV is controversial. Some scholars assert that the ejaculatory duct openings are located at the 5 o'clock and 7 o'clock positions of the seminal colliculus cavity (prostatic utricle) [8,17,18]. Wang et al [19] performed transurethral procedures for 86 patients with benign prostatic hyperplasia or urethral stricture and simultaneously performed transrectal seminal vesicle massage and observed the ejaculatory There were no significant differences in the complications between the two groups (all p > 0.05), but the differences in surgical validity rates between the two groups were statistically significant (*p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The outer layer of the ejaculatory duct is longitudinal smooth muscle. At the proximal end, it becomes thin rapidly, and the inner smooth muscle disappears [8,24]. Therefore, the ejaculatory duct has no sphincter functions, such as peristalsis or contraction, and urinary reflux is prevented only by the presence of the sharp angle between the ejaculatory duct and the prostatic urethra [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a United States study, Nguyen et al (1996) found the mean value of this angle to be 75 . Subsequently, the ducts assumed a straight course until their termination adjacent to the prostatic urethra (Li et al, 2019;López & Angulo, 2013;Malalasekera et al, 2018;McMahon, 1938). In contrast, Banner and Hassler (1978) observed The ducts angulated posterolaterally as they entered the prostate.…”
Section: Resultsmentioning
confidence: 99%
“…Lanka (Malalasekera et al, 2018) and China (Li et al, 2019) described ejaculatory ducts angulating anteromedially within the substance of the prostate as they coursed towards the seminal colliculus. In a United States study, Nguyen et al (1996) found the mean value of this angle to be 75 .…”
Section: Resultsmentioning
confidence: 99%